Values of Moral Education in the Book of Al-Barzanji - Prasetyani U, Winda; Hartati, Yani; Yasirudin, Yasirudin; Sulaiman, Edi; Subing, Zulkarnain; Jaenullah, Jaenullah (Assyfa Journal of Islamic Studies, 2024)
This research aims to explore the values ​​of moral education contained in the book Al-Barzanji, a classic work that describes the life and example of Rasulullah SAW. These moral education values ​​are important because they contribute to shaping an individual's personality and morality based on Islamic teachings. This research uses a qualitative descriptive method with a content analysis approach to identify and describe the moral values ​​contained in the Al-Barzanji text. The research results show that the book Al-Barzanji contains various moral values ​​that are essential for the formation of the character of Muslims. These values ​​include honesty, patience, sincerity and respect, all of which are taken from the noble beliefs of the Prophet Muhammad SAW. Apart from that, this book also emphasizes the importance of love, responsibility and obedience to Allah and His Messenger. This research found that Al-Barzanji is not only a source of spiritual inspiration, but also a practical guide in moral education. The values ​​contained in this book can be applied in everyday life to form individuals with noble character and high morals. The conclusion of this research is that the book Al-Barzanji has great potential as an important source in moral education and character formation among Muslims. By integrating Al-Barzanji's moral values ​​into the educational curriculum, it is hoped that it can help produce a generation that has high morality and is able to face the challenges of the times wisely and ethically.